Business Actors Accountability Model in The Criminal Act of Illegal Logging in Bima NTB - Andriadin Andriadin; Absori Absori; Wardah Yuspin (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
The phenomenal of forest destruction in Bima NTB is motivated by various factors, including agricultural factors, policy factors and inter-regional timber trade systems, business development and timber trade is carried out in unlawful ways such as falsification of forest product documents, logging and timber management without a permit. The purpose of this study is to find out the general description of illegal logging crimes in Bima, prevention efforts and the model of accountability for business actors involved in illegal logging crimes in Bima. The method used in this research is empirical legal research with a socio-legal approach and a case approach (legal approach). Types and sources of data in the form of primary data and secondary data. The results of this study indicate that the model of responsibility imposed on business actors who carry out illegal logging, transportation and processing of wood, in the form of imprisonment and additional penalties, if unable to pay the tax, it will be replaced with imprisonment. This can be seen in the decision of the Raba Bima District Court with the number: 231/Pid. B/LH/2020/PN RBI dated 17 June 2020 in the first alternative indictment the Raba Bima District Court sentenced the defendant TF for violating the provisions of chapter 88 verse 1 letter a Jo. Chapter 16 of law no. 18 of 2013 concerning the prevention and eradication of forest destruction.